Nuclear magnetic resonance of protons on DMSO-02-NaX Zeoli te-system - Hunger, M.; DÂ´Alessandro MartínezA.; Díaz Pérez, L. (Ciencia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> A DMSO O2 NaX-zeolite Â system was studied by pulsed protons NMR technique determining the T1 and T2 ”“ relaxation times, and FID at 10 MHz and 89.5 MHz in a tempetature range between 125 K and 355 K. An isotropic rotation of the methv1 group was proposed influenced by a coupling of the DMSO (dimethylsulphoxide) molecule with the zeolitic lattice for the microdanamic motion of this system.